IoT Based Temperature Monitoring and Mask Scan Entry System: A Review - Aliya Zaki, Shireen Ara, Vaishnavi Akkewar, Ritika Chouhan; Mohammad Nasiruddin (Journal of Electronic Design Engineering, 2021)
The novel coronavirus (covid19) is declared by World Health Organisation (WHO) and the global pandemic has impacted every aspect of life. It affected the industries and economy of major sectors of the whole world and the Internet of Things (IoT) devices make no exception in it. The COVID-19 outbreak has lead to a revised growth forecast for the global economy. Hence to control the spreading virus and to inhibit resurgence of infections, social and technological measures have been implemented towards virus tracing, tracking, etc. The role of IoT in existing digital healthcare infrastructure management has been discussed on how IOT can impact COVID-19 and future pandemics. It is evolving from a conventional healthcare system through which infective can be treated and monitored more easily. Since the pandemic started, there has been a rapid effort in different research communities to exploit a wide variety of technologies to fight this worldwide threat, and IoT technology is one of the explorers in this area.